Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find [tex]\( f(-1) \)[/tex] for the given piecewise function [tex]\( f(x) \)[/tex], we need to evaluate it based on the specified conditions in the piecewise definition:
[tex]\[ f(x) = \begin{cases} -x & \text{if } x \leq 0 \\ x & \text{if } x > 0 \end{cases} \][/tex]
Given that [tex]\( x = -1 \)[/tex]:
1. Determine which condition applies to [tex]\( x = -1 \)[/tex]. Since [tex]\( -1 \leq 0 \)[/tex], we use the first part of the piecewise function [tex]\( -x \)[/tex].
2. Substitute [tex]\( x = -1 \)[/tex] into [tex]\( -x \)[/tex]:
[tex]\[ -(-1) = 1 \][/tex]
Thus, the value of [tex]\( f(-1) \)[/tex] is:
[tex]\[ f(-1) = 1 \][/tex]
Therefore, the answer is:
[tex]\[ f(-1) = 1 \][/tex]
[tex]\[ f(x) = \begin{cases} -x & \text{if } x \leq 0 \\ x & \text{if } x > 0 \end{cases} \][/tex]
Given that [tex]\( x = -1 \)[/tex]:
1. Determine which condition applies to [tex]\( x = -1 \)[/tex]. Since [tex]\( -1 \leq 0 \)[/tex], we use the first part of the piecewise function [tex]\( -x \)[/tex].
2. Substitute [tex]\( x = -1 \)[/tex] into [tex]\( -x \)[/tex]:
[tex]\[ -(-1) = 1 \][/tex]
Thus, the value of [tex]\( f(-1) \)[/tex] is:
[tex]\[ f(-1) = 1 \][/tex]
Therefore, the answer is:
[tex]\[ f(-1) = 1 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.